PERTANGGUNGJAWABAN PIDANA TERHADAP ANAK YANG TURUT SERTA MELAKUKAN PEMBUNUHAN - Rauzatul Fitri; Zulfan Z; Husni H (Fakultas Hukum Universitas Malikussaleh, 2022)
Children need affection which is a psychic need as the most basic need in human life, especially for a child. It is different for minors who must be held accountable for their mistakes for 5 (five) years on the Decision of the Judges of the Takengon District Court. The purpose of this study is to determine the criminal liability of children who participate in murder and to know the legal protection of children who participate in murder according to Article 340 of the Criminal Code. The method used in completing this research is normative juridical. This study uses a conceptual, statutory, and comparative approach. The nature of this research is descriptive, which aims to describe a problem that occurs by interpreting legal materials for problem solving. The results of this study found that in principle children are still subject to criminal responsibility. In the consideration of the Judges of the Takengon District Court, it stated that there was no justification and excuse for abolishing the crime against children, so that children were considered capable of being responsible and found guilty. However, as a child, their rights will still be protected as stipulated in Law Number 35 of 2014 concerning Child Protection (UUPA) where the State, Government, Regional Government, Community, Family, and Parents or Guardians are obliged and responsible for the implementation of Child Protection. Protection of children against perpetrators of crime is very important to do in order to anticipate prevention in the future there will be no more children committing the same crime. Keywords: Children, Criminal Liability, Child Protection, Inclusion